Spatial Distribution Analysis to Identify Hotspot and Lowspot of Antenatal Service Coverage at the Sub-District Level in Jambi Municipality - Lanita, Usi; Perdana, Yulistia Ghita; Syukri, Muhammad (Indonesian Journal of Global Health Research, 2023)
Accelerating the reduction of maternal and child mortality rates can be done by accessing quality maternal health services by antenatal care. This study aimed to identify the spatial distribution pattern of antenatal service coverage in Jambi Municipality in 2019-2021. Global and local Moran Index using Local Indicator for Spatial Autocorrelation (LISA) analysis was used in this study to map hotspots and lowspots of antenatal service coverage. This research used an ecological study with the unit of analysis of all sub-district in Jambi Municipality, totalling 62 sub-districts. Data on antenatal care coverage (K1 and K4) from 2019 to 2021 at the sub-district level were obtained from 20 community health centers. The results of this study found a positive autocorrelation of K1 and K4 from 2019 to 2021. The results of the analysis using LISA found that K1 and K4 coverage hotspots have the same pattern in the northwest direction of Jambi Municipality covering Danau Teluk, Pelayangan, Pasar Jambi districts and K1 and K4 lowspots with the same pattern in the Southwest, Southeast, and South directions covering Alam Barajo and Kota Baru districts. Knowing the pattern of distribution of antenatal service coverage (K1 and K4) can determine the priority areas that need to be improved antenatal service coverage in Jambi Municipality.